Working Paper 48: A collaborative approach to improve business integrity in ASEAN: Case studies of anticorruption Collective Action in the region - Binder, Lucie; Hans, Vanessa; Stransky, Anna (Basel Institute on Governance Working Papers, 2024)
This working paper provides an overview and analysis of anti-corruption Collective Action case studies in the ASEAN region. It builds on the 2014 paper: Collective Action against Corruption: Business and Anti-Corruption Initiatives in ASEAN, which was published by the ASEAN CSR Network and the Asian Institute of Management. This 2023 paper reviews the initiatives featured in the 2014 paper and highlights new initiatives that have emerged in the region since then. It covers: Indonesia: Indonesia Business Links Malaysia: Corporate Integrity System Malaysia Philippines: Integrity Initiative and project SHINE Thailand: Collective Action Against Corruption Thailand: Anti-Corruption Organization of Thailand Vietnam: Vietnam Chamber of Commerce & Industry and its Office for Business The analysis identifies several success factors, while noting that Collective Action is a flexible approach that can and must be tailored to different contexts.